Analysis of vitamin K in green tea leafs and infusions by SPME-GC-FID - Reto, Marcia (2015)
The usual methods for determination vitamin K are laborious. With the aim of replace them by a simpler method that requires fewer solvents, lower analytical levels and allows reporting of results in a smaller period of time, a procedure based on solid-phase microextraction (SPME) and gas chromatography with flame ionization detector (GC-FID) was developed. This method was used to analyse vitamin K in green tea leafs and infusions from nine brands of green tea commercialised in Portugal. The best analytical conditions were obtained using PDMS 7 mu m fibre using immersion extraction at 40 degrees C, for 45 min and 1300 rpm. The linear range for vitamins K1 and K2 was defined. The detection limits obtained with PDMS fibre and GC/FID were 0.16 and 0.07 mg/L for vitamins K1 and K2, respectively. In all analysed infusions the concentration of vitamin K was lower than the detection limit of the developed method, however, the concentration of vitamin K1 present in tea leafs was between 120 and 625 mu g/100 g. (c) 2005 Elsevier Ltd. All rights reserved.